The Bloomsbury Group Memoir Club - Rosenbaum, S. author. aut Link
VIII, 203 p.
Keywords: Shortly before his death, S. P. Rosenbaum began work on the history of the Bloomsbury Group's 'Memoir Club'. With original archival material and valuable insights on leading Bloomsbury figures such as Woolf, Keynes and Forster, this illuminating book offers a new perspective on our understanding of twentieth-century autobiography and life writing.